ANALISIS KINERJA PEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA KOTA MAKASSAR - Adi Siswanto (Jurnal Ilmu Manajemen Profitability, 2020)
This study aims to analyze the performance of employees at the Department of Communication and Information Makassar. The method used in this research is to use qualitative research methods. Data processing procedures in this study use primary data processing sourced from interviews and secondary data processing through theoretical analysis sourced from books, reports, photos, data and observations. The results showed that the results of interviews and observations can be concluded that the ability of employees at the Department of Communication and Information Makassar measured as based on knowledge and skills are still in the category of good enough to support employee performance. Employees understand the work and can finish it in a timely manner. Employee work motivation at the Makassar City Office of Communication and Information in achieving employee performance measured by intrinsic factors (Personal Maturity and Job Satisfaction) and extrinsic factors (Work Environment, Compensation, and Supervision) are in quite good category. Work relations that are established are considered quite close among fellow employees, exemplary leaders who are considered capable of providing motivation. There are still employees who have never attended training in both the leadership and functional technical divisions, therefore it is necessary to immediately provide skills training to employees. It is hoped that employees will more often be given the opportunity to attend training and education. Employees' work motivation at the Makassar City Office of Communication and Information which is categorized as good also did not go unnoticed. Efforts to create a good work environment still need to be improved, especially inadequate compensation. It is hoped that leaders will pay more attention in motivating employees to achieve organizational performance.